The effect of the informational content of share repurchase announcements on their prices depending on the type of shares - ميثم ربيع هادي الحسناوي; سعد مجيد عبد علي الجنابي (Iraqi Journal for Administrative Sciences, 2024)
This study aimed to reveal the impact of repurchase announcements of Common Stock on its Prices in the Formwork of Signal Theory based on the style of stocks , and the role of this theory in explaining processing the informational asymmetry in a way that participates in increasing efficiency of the market and the availability of information to help investors making decisions more accurately, repurchases is a positive signal sent to the market referring to the fact that the stock prices are below their fair value. The study is focused on two main dimensions of the problem for which the following two hypotheses were devised: - • The a style of stock has no relationship on the strength of the signal sent to the market through the repurchasing announcement. • The Kuwait Stock Exchange is not efficient in level a half strong in response to the informational content of the repurchase announcement. The study sample included 170 announcement made by 65 firm listed on the Kuwait Stock Exchange for the period from 1/1/2012 to 24/4/2015. It is worth mentioning that the selection of Kuwait Stock Exchange was a means, not an end, since the foundation end is studying Iraq Stock Exchange but for technical reasons related with the absence of the academic awareness needed for repurchase programs by the firms on the one hand and the dealers in the market from the other hand , this creative mechanism of the policy of payment was not used and the many advantages of it were lost which that can come her of all the parties, which starts with the interests of the individual investor and does not end with bridging the gap of informational asymmetry and improve the efficiency of the market specialized of the rare economy resources . Through the use of various financial and statistical methods using (EXCEL) for analyze the variables of the study and test its hypotheses, the study reached the following conclusions, most important of which is that a style of stock has relationship on the strength of the signal sent to the market through repurchases announcement , and argued on through the results average of the accumulated abnormal return (CAAR) value stocks versus growth stocks . the most effect was of value stocks with great difference , this is contrary to the first hypothesis. The study also proved that there was an inefficient response to the informational content of the repurchase announcement by the Kuwait Stock Exchange, this confirms the market inefficiency in a half strong manner and this supports the truth of second hypothesis of the study . Based on this , the study reached a number of recommendations including necessity of adopting on the signal theory especially in inefficient financial markets to reduce the problem of informational asymmetry between insiders and outside investors.